PENERAPAN MODEL MATEMATIKA PENGUAPAN AIR KERIPIK SUKUN SELAMA DALAM PROSES PENGGORENGAN PADA TEKANAN HAMPA UDARA - Akbar, Muhammad; Kadirman, Kadirman; Jamaluddin P, Jamaluddin P (Universitas Negeri Makassar, 2016)
This research was aimed to know the phenomenon of the water evaporation speed of breadfruits crackers in the vacuum frying process used the mathematic model apply. Breadfruits crackers were fried on the 60 cmHg, 65cm Hg, and 70 cmHg with the duration of frying was 15 minutes, 30 minutes, 45 minutes, and 60 minutes. The parameter of this research was the change water content and water evaporation speed. Data processing was using SPSS version 2.0 and the mathematic model was using Microsoft Excel. The result of the research showed that the vacuum pressure and the duration of the frying process were influential toward the change in the water content and water evaporation speed of breadfruit crackers during frying process in the vacuum pressure. The less the vacuum pressure is the longer the frying process will be the less water content of breadfruit crackers produced